An approach towards energy and material efficient additive manufacturing: Multi-objective optimization of stellite-6 deposition on SS304. (April 2022) - Singh, Anitesh Kumar; Sadhu, Abhijit; Das, Amit Kumar; Pratihar, Dilip Kumar; Roy Choudhury, Asimava
Graphical abstract: Highlights: LEE was improved by 10% with the maximum PDE using multi-optimization technique. Microstructure consisted of dendrite and inter-dendritic eutectics of FCC and HCP phases of cobalt. V o l u m e t r i c w e a r r a t e H a r d n e s s Coating / V o l u m e t r i c w e a r r a t e H a r d n e s s Substrate = 1 / 20 »» Indicated excellent tribological performance of coating. (Rheological factor) Substrate /(Rheological factor) Coating = 3.32 »» Coating has less pile-up and more resistance to deformation. (Coefficient of friction = 0.33) Coating < (Coefficient of friction = 0.5) Substrate . Abstract: Energy and material saving in additive manufacturing (AM) has become the main concern in recent times for sustainable manufacturing. In this study, a 2 kW fiber laser was used in the direct laser metal deposition technique to deposite stellite-6 powder on SS304. Laser power (400–800 W), laser deposition speed (400–800 mm/min) and powder feed rate (10–20 g/min) were considered as input process parameters; whereas laser energy efficiency (LEE), powder deposition efficiency (PDE) and dilution (D) were taken as output responses. An empirical study has been carried out to analyse the combined effect of input process parameters on outputs. Three recently developed multi-objective optimization algorithms were used to maximize LEE and PDE with an optimum dilution, in which Multi-objective bonobo algorithm provided the best Pareto-surface. An improvement of 10% in LEE with maximum PDE was obtained. Microstructure of deposited clad was found to have fine-homogeneous dendrite and inter-dendritic eutectics, which mainly consisted of cobalt phases and carbides. The hardness of the deposited track was found to be three times of that of the substrate, due to the presence of carbides and high cooling rate. The wear rate of the deposited coating was found to be 7.61 × 10 –5 mm 3 /N-m, which was improved 6.6 times to the substrate. A decrease in the pile-up during wear was observed on the deposited surface, which was found to have a correlation with the rheological factor. The ratio of volumetric wear rate to hardness for stellite-6 coating was 1.28 × 10 –7 mm 3 /N-m/HV (20 times less as substrate), which indicated an excellent tribological performance of the coating. A stable friction-wear time curve was observed for stellite-6 coating and the coefficient of friction was found out to be 0.33.